Bioactive peptides from broccoli stems strongly enhance regenerative keratinocytes by stimulating controlled proliferation - Juan Nicolas-Espinosa; Lucía Yepes-Molina; Micaela Carvajal (Taylor & Francis Group, 2022)
Context As the interest on the research of plant derived bioactive peptides (BPs) for nutraceutical, cosmeceutical and medical applications is increasing, in this work, the application of peptide derived from broccoli to keratinocytes was studied. Objective We focussed on the characterization of different peptides hydrolysates from broccoli stems [extracted from total protein (E) and from membrane protein (MF)], and their activity when applied to human keratinocytes. Materials and methods Peptide mixtures from broccoli stems (E and MF) were characterized by proteomics. They were applied to HaCaT cells in order to study cytotoxicity in a concentration range between 20 and 0.15625 µg of protein/mL and wound healing was studied after 24 and 48 h of treatment application. Also, proteomic and gene expression of keratinocytes were analysed. Results Depending on the source, proteins varied in peptide and amino acid composition. An increased proliferation of keratinocytes was shown after the application of the E peptides mixtures, reaching 190% with the lowest concentrations, but enhanced wound healing repair with E and MF appeared, reaching 59% of wound closure after 48 h. At the gene expression and protein levels of keratinocytes, the upregulation of anti-oncogene p53 and keratinization factors were observed. Discussion These results suggest that peptide mixtures obtained from broccoli augmented cell proliferation and prevented the carcinogenic, uncontrolled growth of the cells, with different mechanisms depending on the protein source. Conclusions The results encourage the opening of new lines of research involving the use of Brassica peptides for pharmaceutic or cosmetic use.